Measurement error in longitudinal earnings data: Evidence from Germany - Achim Schmillen; Matthias Umkehrer; Till von Wachter (Journal for Labour Market Research, 2024)
We present evidence on the extent of measurement error in German longitudinal earnings data. Qualitatively, we confirm the main result of the international literature: longitudinal earnings data are relatively reliable in a cross section but much less so in first differences. Quantitatively, in the cross section our findings are very similar to those of Bound and Krueger (J Labor Econ 9:1-24, 1991) and Pischke (J Bus Econ Stat 13:305-314, 1995) for the United States while we find even stronger evidence that first-differencing exacerbates measurement error problems. We also show that measurement error in our survey data is not "classical" as it is negatively correlated with administrative earnings and positively autocorrelated over an extended period of time. Additionally, we estimate a model of measurement error stemming from underreporting of transitory earnings shocks in combination with a white-noise component and make a number of methodological contributions. Our results are robust to the use of two different linked survey-administrative data sets and various other sensitivity checks.
Keywords: C33; C18; J30; 330; Earnings dynamics; Linked survey-administrative data; Measurement error; Transitory and permanent earnings